Identification of Potential Performance-Related Predictors in Young Competitive Athletes - Blume, Katharina; Wolfarth, Bernd (Frontiers in Physiology, 2019)
Introduction Systematic training is an essential demand for the individual success of an athlete. However, similar training modalities cause individual responses, and finally, decide on athletes’ success or failure. To predict performance development, potential influencing parameters should be known. Therefore, the purpose of this study was to identify performance-related parameters in young competitive athletes. Methods Individual performance developments of 146 young athletes (m: n = 96, f: n = 50, age V1: 14.7 ± 1.7 years) of four different sports (soccer: n = 45, cycling: n = 48, swimming: n = 18, cross-country skiing: n = 35) were evaluated by analysis of 356 visits in total (exercise intervention periods, 289 ± 112 d). At V1 and V2 several performance parameters were determined. Based on the relative performance progress (Δ), potential influencing predictors were analyzed: training load, health sense, stress level, clinical complaints, hemoglobin, vitamin D, hs-CRP and EBV serostatus. Data were collected within a controlled, prospective study on young athletes, which was conducted between 2010 and 2014. Results Athletes improved their performance by 4.7 ± 10.7%. In total, 66.3% of all athletes represented a positive performance progress. This group demonstrated, despite similar training loads (p = 0.207), enhanced health senses (p = 0.001) and lower stress levels (p = 0.002). In contrast, compared to athletes with an impaired performance progress, no differences in hemoglobin values (m: p = 0.926, f: p = 0.578), vitamin D levels (0.787) and EBV serostatus (p = 0.842) were found. Performance progress was dependent on extents of health senses (p = 0.040) and stress levels (p = 0.045). Furthermore, the combination of declined health senses and rised stress levels was associated with an impaired performance development (p = 0.018) and higher prevalences of clinical complaints (p < 0.001) above all, in contrast to hs-CRP (p = 0.168). Discussion Athletes with an improved performance progress reported less pronounced subjective sensations and complaints. In contrast, objective known performance-related indicators, offered no differences. Therefore, subjective self-reported data, reflecting health and stress status, should be additionally considered to regulate training, modify intensities, and finally, predict and ensure an optimal performance advance.